P1298 A conservative strategy for an uncommon complication of endocarditis. (17th January 2020) - Ferreira, J; Freitas, A; Gardete, S; Simoa, G; Ferreira, H; Simoes, J; Beringuilho, M; Faria, D; Roque, D; Morais, C
Abstract: : A 64-year-old man was admitted for aortic valve prosthesis endocarditis. He had relevant personal medical history of mechanical aortic valve implantation 6 years before, coronary arterial disease with bypass graft surgery, chronic kidney disease on haemodialysis (with a need to implantation of long-duration haemodialysis catheter due to arteriovenous fistula thrombosis), Diabetes mellitus type 2 for 20 years, peripheral artery disease and ischemic stroke 2 years before. He presented with a medical history of fever without evident clinical origin. From the diagnostic workup there were 4 blood cultures positive for methicillin-resistant Staphylococcus epidermidis. The bacteraemia was considered to be originated from the haemodialysis catheter and a new one was implanted. Transthoracic echocardiogram (TTE) at admission showed aortic anterior annulus dissection with an extensive dehiscence area (figure top-left). Subsequent evaluations showed fistulisation of the pseudoaneurysm to the right ventricle outflow tract (RVOT) (figure top-right and bottom-left) and the pulmonary trunk (PT) (figure bottom-right), as well as images compatible with vegetations at the septal cuspid of the pulmonary valve (figure yellow arrow). Furthermore, there was compromised right ventricle longitudinal systolic function and moderate tricuspid regurgitation with an estimated systolic pulmonary artery pressure of 80mmHg. Left ventricle systolic function was preserved and prothesis had no obstruction. Case was discussed with cardiothoracic surgery from 2 centres and both considered that the surgical risk was too high. Patient was treated in a conservative way with rifampicin and gentamicin for 15 days and also with vancomycin ad eternum (after haemodialysis sessions). Blood cultures at discharge were negative. He remained hemodynamically stable and with no evidence of heart failure during admission. Subsequent ambulatory clinical and echocardiographic monitoring was unremarkable in regarding to endocarditis, with no evidence of progression of endocarditis as well as no signs or symptoms of heart failure. Patient died 10 months later due to sepsis originated on a lower limb infection of irreversibly ischemic tissue (patient had refused amputation before). Discussion: Infective endocarditis of mechanical prosthesis has different presentations depending on the involvement of prosthesis and periprosthetic structures, and it is associated with high morbidity and mortality. Pseudoaneurysm of the intervalvular fibrosa is an uncommon complication, furthermore when complicating with dissection to near structures such as RVOT and the PT in this case. Treatment is mainly surgical, however, in this case the surgical risk was too high due to comorbidities and a conservative strategy was adopted. It seems that it was a reasonable strategy as the patient evolution was unremarkable when regarding endocarditis. Unfortunately, he ended up dying from probably unrelated complications.